Communication Strategy of Diskominfo Magetan Regency in Socializing SP4N-LAPOR! to the Public in 2022-2023 - Rukma, Anggit Ambar; Sofyan, Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
National Public Service Complaint Management System (SP4N) - People's Online Aspiration and Complaint Service (LAPOR!) is a service for conveying all the aspirations and complaints of the Indonesian people through several complaint channels, namely the website www.lapor.go.id, SMS 1708 (Telkomsel, Indosat, Three), Twitter @lapor1708 as well as mobile applications (Android and iOS) that connect the community with the government, especially in Magetan Regency. This research aims to explain how the Diskominfo Magetan Regency implements communication strategies through five stages in the SP4N-LAPOR! Service socialization activities. The importance of this research is based on obstacles related to the not-yet-optimal use of the SP4N-LAPOR! by the people of the Magetan Regency. So, the Diskominfo Magetan Regency a government agency responsible for information management, must carry out outreach activities related to this complaint service. This research uses a qualitative descriptive method with a post-positivistic paradigm, testing data validity through source triangulation techniques and data analysis, including data collection, data reduction, data presentation, and conclusion. The results of this research are that the Diskominfo Magetan Regency is considered effective in implementing communication strategies in socialization activities and obtaining results by program objectives through five communication strategies: research, planning, implementation, evaluation, and reporting. This success was marked by an increase in the number of complaints recorded on the SP4N-LAPOR! at Diskominfo Magetan Regency compared to the previous year. The limitation of this research is that the researcher could only answer phenomena related to communication strategies carried out by the Diskominfo Magetan Regency and could not answer wonders of communication strategies in other government agencies in socializing the SP4N-LAPOR! Service To the Public in 2022-2023.